BIOEFFICACY OF PLANT EXTRACTS ON GROWTH OF BOTRYTIS CINEREA CAUSING LEAF BLIGHT OF ROSE - M. B. WAGHMARE; R. M. WAGHMARE; S. S. KAMBLE (The Bioscan, 2011)
25 % Alcoholic leaf extract of Melia azedarach L., Clerodendrum inerme L., Hyptis suaveolens, Tagetes erecta L. and Swietenia macrophylla King were found to be effective in controlling the growth of sensitive and resistant isolates of Botrytis cinerea causing leaf blight of rose. While aqueous leaf extract of Hyptis suaveolens and Tagetes erecta inhibited growth of both sensitive and resistant isolates of Botrytis cinerea at 50 %.